Kejahatan Transnasional Di Indonesia: Studi Kasus Yakuza Sebagai Organisasi Kejahatan Internasional - Rusli, Adi Saputra; Iswahyudi Mansur, Yanwar; Arumdanie, Nisrina; Mubarok, Biky Uthbek (UI Scholars Hub, 2023)
This article presents an analysis of the Yakuza phenomenon, an organized crime organization with deep historical roots in Japan. Through a qualitative approach, this research explores the history and development of the Yakuza, their criminal focus, operational networks, and their impact both national and international levels. The Japanese government's efforts to combat the Yakuza, on a national and global scale, are detailed, including programs for drug prevention, anti-human trafficking, and counter-terrorism. In an international context, the Yakuza is known for its extensive networks, creating new challenges in global security. This research also highlights the importance of global efforts to counter the negative impacts of the Yakuza. The article provides an in-depth understanding of the complexity of this criminal organization and raises crucial questions regarding the Yakuza's impact beyond Japan, including in Indonesia. With rapid economic growth and global connectivity, Indonesia emerges as a potential site for the infiltration of international criminal organizations. Therefore, the article emphasizes the need for increased security measures in Indonesia to prevent the negative impacts of the Yakuza. This conclusion underscores the urgency of a global response to combat the existence of the Yakuza, ensuring the national resilience of Indonesia and global security.